Pension privatization and country risk - Cuevas, Alfredo (IMF working paper ;, 2008)
This paper explores how privatizing a pension system can affect sovereign credit risk. For this purpose, it analyzes the importance that rating agencies give to 'implicit' pension debt (IDP) in their assessments of sovereign creditworthiness. We find that rating agencies generally do not seem to give much weight to IPD, focusing instead on 'explicit' public debt. However, by channeling pension contributions away from the government and creating a deficit of resources to cover the current pension liabilities during the reform's transition period, a pension privatization reform may transform IPD into explicit public debt, adversely affecting a sovereign's perceived creditworthiness, thus increasing its risk premium. In this light, accompanying pension reform with efforts to offset its transition costs through fiscal adjustment would help preserve a country's credit rating.